Addressing the Double Burden of Malnutrition in ASEAN - Mbuya, Nkosinathi Vusizihlobo; Osornprasop, Sutayut; David, Clarissa (World Bank, Bangkok, 2020)
Malnutrition, which encompasses both undernutrition and overnutrition, presents a significanthuman capital as well as economic development challenge across most ASEAN Member States.A healthy, well-nourished, well-educated and skillful population provides the foundation for aproductive life and enables future workers to compete in the dynamic labor markets of digitaleconomies. However, most of ASEAN's lower-income countries face an unfinished agenda withregard to undernutrition. Undernutrition elevates the risk of infant and child morbidity andmortality, increases expenditure on health care and social safety nets, lowers the efficiency ofinvestments in education, and decreases lifelong income-earning potential and labor forceproductivity, with the potential to be transmitted across generations. Estimates for some ASEANmember states show undernutrition resulting in annual losses of between 2.4 percent - 4.4 percent of GDP Overnutrition compounds the challenges. Overnutrition is posing an increasing challenge to ASEAN, with some countries having high prevalence of obesity and overweight. In the last 35 years obesity prevalence across ASEAN increased over 7-fold, most rapidly in Cambodia, Indonesia, and Lao PDR, where obesity rates have risen more than 10-fold. Childhood overweight and obesity is likewise a growing problem, especially in Brunei, Malaysia, and Thailand where childhood overweight prevalence exceeds 25 percent. Overweight and obesity among ASEAN member states have high direct costs for some countries, for example in Brunei it is 16. Direct health care costs related to treatment of obesity and associated chronic diseases due to obesity as well as indirect costs, particularly from the loss of labor productivity, are expected to increase in many ASEAN countries.